A rare case of large ovarian ectopic pregnancy managed by fertility preserving surgery - Jahagirdar, Sayali S.; Patil, Kshwelati R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Ectopic implantation of fertilized egg in the ovary is rare. Risk factors are similar to those for tubal pregnancies. Presenting complaints and findings mirror those for tubal ectopic pregnancy. Although the ovary can accommodate the expanding ovarian pregnancy more easily than fallopian tube, rupture at an early stage is the usual consequence. Diagnosis may not be made until surgery or by the pathologist as an early ovarian pregnancy may be mimic haemorrhagic corpus luteum. Use of transvaginal sonography has resulted in a more frequent diagnosis of unruptured ovarian pregnancy. Sonographically, an internal anechoic area is surrounded by wide echogenic ring, which in turn is surrounded by ovarian cortex is suspicious of ovarian ectopic. Diagnosis of ovarian pregnancy has a specific criterion outlined by Spiegelberg in 1878. Treatment has been surgical for almost all known ovarian ectopic pregnancies. Small lesions may be managed by ovarian wedge resection or cystectomy, whereas larger lesions require oophorectomy. In a few cases of unruptured small ovarian ectopics, have been managed by methotrexate therapy with successful outcome. Here we presented a case of primigravida having large ovarian ectopic successfully managed by excising ectopic pregnancy alone.